Thermally-Activated Vortex Motion and Electrical Dissipation in a Bi2Sr2CaCu2Oδ Thin Film - de la Cruz, C. R.; dela Cruz, A. P. C.; Guerra, L. J. D.; Sarmago, R. V. (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
The magnetoresistance, obtained from resistivity measurements with external magnetic fields up to 0.5T, was used to directly measure and investigate the electrical dissipation properties of a c-axis oriented Bi2Sr2CaCu2O8+δ thin film. An activation-related “peaked” profile below Tc was observed in the magnetoresistance. In increasing applied magnetic field, the peak shifts to lower temperatures, broadens, and becomes more asymmetric. The analysis, made based on an Arrhenius-type activation mechanism, shows that the activation energy decreased with increasing applied magnetic field, as predicted by the Anderson-Kim Thermally-Activated Flux Creep Theory. Therefore, in these low magnetic fields and temperatures, the vortex motion predominant in the films is thermally activated and contributes largely to the dissipation in these films.